Evaluasi Perda Nomor 44 Tahun 2002 Tentang Ketenteraman dan Ketertiban di Kelurahan Lima Belas Ilir, Kecamatan Ilir Timur I - Ardiansyah Ardiansyah; Alamsyah Alamsyah; Mega Nugraha (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Ardiansyah. Evaluation of Regional Regulation Number 44 of 2002 concerning Peace and Order in Lima Belas Ilir Village, East Ilir I District. This study aims to: 1) Analyze and describe the Evaluation of Regional Regulation Number 44 of 2002 concerning Peace and Order in Lima Belas Ilir Village, East Ilir I District; 2) Analyze and describe the Supporting and Hindering Factors for the Evaluation of Regional Regulation No. 44 of 2002 concerning Peace and Order in Limabelas Ilir Village, East Ilir District I. The research design used in this study is qualitative descriptive. Descriptive research can be interpreted as a problem-solving procedure that is investigated by describing / describing the state of the subject/object of research (a person, institution, society and others) at the present time based on facts that appear or as they are (Nawawi in Klicit, 2008). The results of the study concluded that: 1) The implementation of Regional Regulation No. 44 of 2002 concerning Peace and Order in Limabelas Ilir Village, Ilir Timur I District has not been optimal so far. Problems related to peace and order still often occur, such as thuggery and violations by street vendors that disturb public order and order. Education has been carried out many times through socialization and approaches through local community leaders, but the number of violations has not been able to be suppressed and is still occurring. Related to this, the lack of a high level of public awareness in complying with the regulations is considered to be the main cause of frequent violations, plus the lack of optimal enforcement of violations committed, so that violators are not deterred and tend to be ordinary in committing violations; 2) Supporting Factors for the Evaluation of Regional Regulation No. 44 of 2002 concerning Peace and Order in Fifteen Ilir Village, East Ilir District I is the existence of clear rules or legal basis contained in Regional Regulation No. 44 of 2002 concerning Peace and Order itself, then the high commitment shown by the employees of the Fifteen Ilir Village Office. Meanwhile, the inhibiting factor is that there are still many residents of Lima Belas Ilir Village who do not understand Regional Regulation Number 44 of 2002, the level of public awareness in complying with regulations is still lacking, lack of supervision from related parties, so that in the implementation of Regional Regulation Number 44 of 2002 has not been able to be applied properly, and the approach taken to the community is still not optimal.